2020
DOI: 10.1038/s41598-019-56800-5
|View full text |Cite
|
Sign up to set email alerts
|

New predictions of 137Cs dynamics in forests after the Fukushima nuclear accident

Abstract: Most of the area contaminated by the Fukushima Daiichi Nuclear Power Plant accident is covered by forest. In this paper, we updated model predictions of temporal changes in the 137Cs dynamics using the latest observation data and newly provided maps of the predicted 137Cs activity concentration for wood, which is the most commercially important part of the tree body. Overall, the previous prediction and latest observation data were in very good agreement. However, further validation revealed that the migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…[ 30 ]. In addition, previous studies have made significant contributions to addressing the reasons for the lack of activity reductions over time [ 28 , 31 ]. Hashimoto S, et al [ 31 ] investigated whether the 137 Cs concentration of wild mushrooms would be spatially biased or influenced by the 137 Cs or exchangeable potassium concentrations in soils because the concentration fluctuates among the same species growing within a given area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 30 ]. In addition, previous studies have made significant contributions to addressing the reasons for the lack of activity reductions over time [ 28 , 31 ]. Hashimoto S, et al [ 31 ] investigated whether the 137 Cs concentration of wild mushrooms would be spatially biased or influenced by the 137 Cs or exchangeable potassium concentrations in soils because the concentration fluctuates among the same species growing within a given area.…”
Section: Discussionmentioning
confidence: 99%
“…[30]. In addition, previous studies have made significant contributions to addressing the reasons for the lack of activity reductions over time [28,31].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The role of forests as a potential perennial supply of sediment and associated 137 Cs to river systems in this region in general, and in the more densely inhabited coastal areas in particular, remains one of the main challenges for investigation in the future. After complex processes of transfer and migration of 137 Cs from the canopy, the tree trunk, and the litter to mineral horizons of soils beneath woodlands [Hashimoto et al, 2020], forests may continue supplying contaminated material to rivers and ultimately to the Pacific Ocean, where 137 Cs may desorb [Takata et al, 2020] and it may incorporate marine biota or seafloor sediment [Buesseler, 2020]. Accordingly, the reduction in potential downstream transfers of 137 Cs from forested regions through remediation and/or ongoing 137 Cs management will likely be an important priority for local inhabitants [Koarashi et al, 2020].…”
Section: Perspectives For Regional Recovery Inmentioning
confidence: 99%
“…Consequently, the radioactive cesium-137 with a half-life of 30 years caused contamination that was a serious concern because of the deleterious effect of radioactive cesium-137 on the environment or on humans [2][3][4]. Radioactive cesium-137 has been found in contaminated soil [5], forest [6], seawater [7][8][9], and freshwater [10], In addition, there are several reports that showed that radioactive cesium-137 has contaminated seawater sheries. Wada et al2013 determined that radioactive cesium contamination had occurred in marine products that took place during April 2011 to October 2012.…”
Section: Introductionmentioning
confidence: 99%